[Budget Procedure and Agreements, Weekly Student Contact Hour Assignments and Definitions, Cypress College, 1974-75.] - Scheidt, Omar H.; North Orange County Community Coll. District, Fullerton, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Information related to the budgets of Cypress College and Fullerton College is provided in this report. The sections of the report are: Budget Agreements, 1974-75, North Orange County Community College District: Definitions and Formulas (Cypress College and Fullerton College); Budget Procedure, Cypress College (Capital Outlay Budget, Operations Budget, Community Services Budget, Class Related Programs and Activities Budget, and Budget Procedures Flowchart); and Budgeting Agreements, 1974-75, Cypress College (Definitions and Projections of WSCH--Weekly Student Contact Hours, and Division and College WSCH Assignments, 1974-75). (DB)
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Budgets; Community Colleges; Educational Finance; Postsecondary Education; Research Reports; Scheduling; Cypress College CA -- Fullerton College CA; Reports, Research